Submucosal stone formation after 14-years of polydimethylsiloxane (Macroplastique®) endoscopic subureteric injection for vesicoureteral reflux: Unusual presentation for a rare complication - Aljumaiah, Sahar (Urol Case Rep, 2020)
Polydimethylsiloxane (Macroplastique®) endoscopic subureteric implantation is considered to be safe and effective for vesicoureteral reflux (VUR) treatment. The Macroplastique® implantation is popular for its high success rate and minimal complications. A 22-years-old male who underwent prior subureteric endoscopic therapy with Macroplastique for VUR 14-years ago was investigated for microscopic hematuria. Renal ultrasound confirmed the presence stone that was retrieved by cystolitholapaxy. Although endoscopic subureteric implantation with Macroplastique has a high success rate for VUR resolution, caution during the follow-up period in order to prevent potential long-term complications is required.